STRATEGI KOMUNIKASI POLITIK DPD PARTAI GOLKAR PADA PEMILU LEGISLATIF ACEH TENGAH 2019 - Basri, Hasan (Master of Communication Science Program, Universitas Diponegoro, 2021)
This research focuses on the political communication strategy of the Golkar DPD in the 2019 Central Aceh legislative elections. A political communication strategy is very important for a political party that wants to attract sympathy to get people's approval. This study adopts a qualitative approach that describes and explains the political communication strategy of the Golkar legislative electoral council. Golkar as one of the parties involved in the competition and winning the 2019 Central Aceh Pilkada won four DPRK seats. The political communication strategy carried out by Golkar in winning the 2019 Election is for Golkar to listen to and convey the aspira-tions of the people. The political communication strategy implemented by the Golkar party in the legislative elections is structured communication from the central leader-ship to cadres in rural areas so that political messages can be conveyed equally, in the face of the 2019 legislative elections, Golkar provides information to people who have the right to vote, educate the public, accommodate the aspirations of the commu-nity, and socializing aimed at the government and other political institutions, the board of DPD Golkar to convey all forms of work programs to the public, as a means of party political communication such as providing information to the mass media. People who do not receive messages and do not want to communicate with Golkar party cadres because they are not interested in political activities, people who are more interested in political manipulation, and people who already have candidates from close relatives.